MIDWIFERYCAREFORMATERNITYWTAHANINTEVENTION FOCUS OF PROVISIONING LAVENDER AROMATHERAPY RELAXATION DISTRACTION TECHNIQUES IN THE I TIME OF LABOR IN PUSKESMAS TOROH I - Ica Tasnia; Nurul Kodiyah; Laily Himawati (Lppm Unan, 2023)
Background; Labor is the process of opening and thinning the cervix, as well as uterine contractions, and the fetus descends into the birth canal, causing pain in labor. Labor pain is a physiological process caused by contractions that cause cervical dilatation. Pain can be eliminated pharmacologically and non-pharmacologically, non-pharmacologically by giving lavender aromatherapy relaxation distraction. This study aims to determine the effect of lavender aromatherapy relaxation distraction on reducing back pain in latent stage 1 labor. Method; The research design that the researcher uses is a case study research design. This type of descriptive case study research uses participatory observation method. The subjects in this study were mothers during the 1st stage of the latent phase. Result; The results showed that the diagnosis of Ny. S with back pain disorder. Evaluation of giving lavender aromatherapy relaxation distraction in the case of Ny. S with pain can be resolved and reduce pain at the time of delivery from a scale of 7-9 to 4-6. Conclusion; The problem of first stage labor in Ny. S is resolved.